Clozapine and Pneumonia: Synthesizing the Link by Reviewing Existing Reports—A Systematic Review and Meta-Analysis - Victor Zhao; Yiting Gong; Naveen Thomas; Soumitra Das (Medicina)
Background and Objectives: Clozapine is a highly effective antipsychotic used for treating treatment-refractory psychotic and mood disorders. However, clozapine also has a serious risk of side effects leading to mortality, particularly its potentiated risk of leading to pneumonia. This review aims to overview the demographic and health-related risk factors leading to pneumonia to better inform risk assessment for clozapine users and to summarise current theories on the mechanisms for clozapine-associated pneumonia. This paper will highlight the need to prioritise pneumococcal vaccination in this population group. Materials and Method: We conducted a literary search of five online databases conforming to PRISMA. Our review includes all peer-reviewed papers with original data that discuss clozapine and pneumonia and excludes case reports. Baseline information of participants, pneumonia-related information and information regarding risk factors and mechanisms causing pneumonia were also extracted. Results: Clozapine was found to have an increased risk of pneumonia compared to other antipsychotic medications. Factors included comorbidities, higher clozapine dosages, and concurrent use of other antipsychotic medications. Key mechanisms for clozapine-associated pneumonia include clozapine-induced hyper sedation, sialorrhea and neutropoenia. Conclusions: While clozapine improves overall mortality for patients, our review confirms clozapine has the highest risk of pneumonia of all antipsychotics. The review also highlights the prevalent underuse of pneumococcal vaccines among clozapine users and the urgent need to increase uptake.